Karon's Case of "Mr. X" and the "International Society for the Psychological Treatments of Schizophrenia and Other Psychoses" (ISPS) - Silver, Anne-Louise S. (Pragmatic Case Studies in Psychotherapy, 2008)
This Commentary on the case study of Mr. X places Bertram Karon’s (2008) work in the contexts of (a) the current treatment of people suffering from psychotic disorders; (b) Karon’s historical connections with the ideas of such pioneering, humanistically oriented, psychodynamic psychiatrists as Frieda Fromm-Reichmann and Sándor Ferenczi; (c) the mission and work of the International Society for the Psychological Treatments of Schizophrenia and Other Psychoses (ISPS) and its U.S. chapter (ISPS-US); and (d) the ongoing struggle in psychiatry over the evidential legitimacy of the psychodynamic treatment of psychosis and schizophrenia. I conclude by pointing out that empirical details about process and outcome in the psychodynamic treatment of schizophrenia as documented in cases like Karon’s help to provide one source of such evidential legitimacy.